Weather-based yield prediction in banana (Musa spp.) by using principal component analysis (Current Horticulture, 2024)
Banana (Musa spp.) production is greatly  influenced by weather parameters. Accurate weather based yield forecast helps planners and policy makers. Weather-based yield prediction models  provide a trustworthy yield forecast, and also helps in  forewarning of pest and diseases (Agrawal and Mehta,  2007). According to Salau et al., 2016 excessive rainfall  and extremely high temperature can reduce banana  productivity, while production is also small when  both rainfall and temperature are very low with poor  humidity. Information on yield climate relationship  helps in forecasting yield and formulating suitable  policies. Yield prediction or forecasting is an important  aspect of developing economy so that proper planning  can be undertaken for the sustainable growth.
Keywords: Weather-based; prediction